Comparison of Gene Editing Versus Conventional Breeding to Introgress the POLLED Allele Into the Tropically Adapted Australian Beef Cattle Population - Mueller, Maci L.; Cole, John B.; Connors, Natalie K.; Johnston, David J.; Randhawa, Imtiaz A. S.; Van Eenennaam, Alison L. (Frontiers in Genetics, 2021)
Dehorning is the process of physically removing horns to protect animals and humans from injury, but the process is unpleasant, costly and faces increasing public scrutiny. Genetic selection for polled (hornless), which is genetically dominant to horned, is a long-term solution to eliminate the need for dehorning. However, due to the limited number of polled Australian Brahman bulls, the northern Australian beef cattle population remains predominantly horned. The potential to use gene editing to produce high-genetic-merit polled cattle was recently demonstrated. To further explore the concept, this study simulated introgression of the POLLED allele into a tropically-adapted Australian beef cattle population via conventional breeding or gene editing (top 1% or 10% of seedstock bulls/year) for 3 polled mating schemes and compared results to baseline selection on genetic merit (Japan Ox selection index, $JapOx) alone, over the course of 20 years. The baseline scenario did not significantly decrease the 20-year HORNED allele frequency (80%) but resulted in one of the fastest rates of genetic gain ($8.00/year). Compared to the baseline, the conventional breeding scenarios where polled bulls were preferentially used for breeding, regardless of their genetic merit, significantly decreased the 20-year HORNED allele frequency (30%) but resulted in a significantly slower rate of genetic gain ($6.70/year, P ≤ 0.05). The mating scheme that required the exclusive use of homozygous polled bulls, resulted in the lowest 20-year HORNED allele frequency (8%), but this conventional breeding scenario resulted in the slowest rate of genetic gain ($5.50/year). The addition of gene editing the top 1% or 10% of seedstock bull calves/year to each conventional breeding scenario resulted in significantly faster rates of genetic gain (up to $8.10/year, P ≤ 0.05). Overall, our study demonstrates that, due to the limited number of polled Australian Brahman bulls, strong selection pressure on polled will be necessary to meaningfully increase the number of polled animals in this population. Moreover, these scenarios illustrate how gene editing could be a tool for accelerating the development of high-genetic-merit homozygous polled sires to mitigate the current trade-off of slower genetic gain associated with decreasing HORNED allele frequency in the Australian Brahman population.